1995
DOI: 10.1002/ijc.2910610312
|View full text |Cite
|
Sign up to set email alerts
|

α‐interferon potentiates epidermal growth factor receptor‐mediated effects on human epidermoid carcinoma KB cells

Abstract: The molecular mechanisms underlying the growth inhibition of human tumor cells induced by recombinant interferon-alpha (IFN alpha) are mostly unknown. It has been proposed that this effect could be related to down-regulation and/or impaired function of peptide growth factor receptors (PGF-Rs) in tumor cells exposed to IFN alpha. However, we have previously described that IFN alpha-induced growth inhibition of human epidermoid carcinoma cells is paralleled by up-regulation of epidermal growth factor receptor (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…We have previously reported that the treatment with 1000 IU/ml IFNa for 48 h induces 50% growth inhibition and EGF-R upregulation on KB cells. 5 We have found that, at these experimental conditions, 40% of IFNa-treated KB cells were apoptotic as demonstrated by internucleosomic DNA fragmentation and quantitized by FACS analysis after nuclear dye with propidium iodide ( Figure 1C, F and G). Apoptosis induction was further demonstrated by TUNEL technique ( Figure 2B).…”
Section: Apoptosis Was Induced By Ifna and Antagonized By Egf In Kb Cmentioning
confidence: 78%
See 2 more Smart Citations
“…We have previously reported that the treatment with 1000 IU/ml IFNa for 48 h induces 50% growth inhibition and EGF-R upregulation on KB cells. 5 We have found that, at these experimental conditions, 40% of IFNa-treated KB cells were apoptotic as demonstrated by internucleosomic DNA fragmentation and quantitized by FACS analysis after nuclear dye with propidium iodide ( Figure 1C, F and G). Apoptosis induction was further demonstrated by TUNEL technique ( Figure 2B).…”
Section: Apoptosis Was Induced By Ifna and Antagonized By Egf In Kb Cmentioning
confidence: 78%
“…2 ± 4 We have also demonstrated that the proliferative response of human epidermoid cancer KB cells to EGF is increased by IFNa. 5 This latter effect is paralleled by an increased tyrosine phosphorylation of cellular proteins and of the EGF-R itself in KB cells exposed to IFNa; 5 it is suggested that the EGF-R signalling is upregulated in IFNatreated tumour cells. 5 We have speculated that the enhanced expression and function of EGF-R by the tumour cells could represent a stress response that might be activated as an attempt to provide an escape mechanism to the growth inhibition induced by IFNa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGF-R up-regulation has also been reported after tumour cell treatment with low doses of adriamycin or retinoic acid (Jetten, 1980;Zuckier and Tritton, 1983). Furthermore, IFN-α, but not ARA-C, potentiates the growth-promoting effect of EGF in KB cells while inducing EGF-R up-regulation (Caraglia et al, 1995). On this basis, we have hypothesized that up-regulation of growth factor receptors is a common event in growth-inhibited tumour cells and could represent a protective response towards the antiproliferative stimuli (Tagliaferri et al, 1994).…”
Section: Discussionmentioning
confidence: 89%
“…We have selected as experimental model the KB epidermoid carcinoma cell line that is responsive to the mitogenic stimulus induced by EGF (Aboud-Pirak et al, 1988;Caraglia et al, 1995) and is growth inhibited by 8-Cl-cAMP treatment. We have found that the growth-promoting activity of EGF on KB cells was completely abolished by 8-Cl-cAMP.…”
mentioning
confidence: 99%